The United States-Nigerian Military Co-operation and Adherence to Rules of Engagement by the Nigerian Military during Internal Security Operations, 1999-2020 - Obikaeze, Chibuike Victor; Nwokoye, Agary Ndubuisi; Manasseh, Bassey; Efanodor-Obeten, Omokiniovo Harriet (Journal of Contemporary International Relations and Diplomacy, 2023)
Despite United States-Nigeria military cooperation which has provided an opportunity for professional training of the Nigerian military, particularly in the area of ‘rules of engagement’, there has been series of reported human rights violations in Nigeria. This usually takes place during internal conflicts that necessitate the intervention of the military. There has been non-adherence to international humanitarian law as well as weak enforcement of national legal frameworks pertaining to human rights. The study examined how the U.S. professional training has reoriented the Nigerian Armed Forces regarding respect and protection of human rights in conflict situations. The study adopted ‘case study’ method that focuses on few cases in order to engage in an empirical analysis. There still existing lacunas in the operations of the Nigerian armed forces regarding protection and respect of the rights of civilians. Thus, there have been widespread and pervasive human rights abuses perpetrated by the Nigerian military which have resulted to arbitrary killings, tortures, rapes and so forth. Sadly, the Nigerian state provides shield to the perpetrators of unlawful acts that pervert the basic rules of engagement. Absence of effective rule of law in Nigeria emboldens the army in particular, to perpetuate colossal human rights violations. The paper argues that the behavioural patterns of the Nigerian military would remain unchanged until the character of the Nigerian state changes. There should be a strong recall of rule of law by establishing strong institutions where the justice system in Nigeria is viable enough to control the state itself.